Ceny sprzedaży ziemi rolniczej Skarbu Państwa w województwie zachodniopomorskim - Kiszczak, Leokadia; Szczecińska, Beata (Selling Prices of Treasury's Agricultural Grounds in Westpomeranian Voivodship, 2005)
The Agricultural Property Agency uses different forms of management on the agriculture grounds being under its supervision. One of the forms is sale of the grounds. The subject of the article is the analyse of selling prices of the agricultural State's Treasury ground through years 1997-2004 in the area of Regional Branch of the Agency in Szczecin. The results do not give a clear picture concerning the trend in prices of agricultural grounds during the period.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 425-430